Sodium–glucose co‐transporter‐2 inhibitor cardiovascular outcome trials and generalizability to English primary care. Issue 9 (28th March 2020) - Hinton, W.; Feher, M.; Munro, N.; Joy, M.; de Lusignan, S.
Abstract: Aim: To identify people in English primary care with equivalent cardiovascular risk to participants in the sodium–glucose co‐transporter‐2 inhibitor (SGLT‐2i) cardiovascular outcome trials (CVOTs). A secondary objective was to report the usage of SGLT‐2is. Methods: Cross‐sectional analysis of people registered with participating practices in the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) network on the 31 December 2016. We derived: (1) proportions of the primary care population eligible for inclusion in each SGLT‐2i CVOT (CANVAS, DECLARE, EMPA‐REG and VERTIS); (2) characteristics of the eligible population compared with trial participants (demographics, disease duration and vascular risk); and (3) differences within the eligible population prescribed SGLT‐2is. Results: The proportions of people with type 2 diabetes ( N = 84 394) meeting the inclusion criteria for each CVOT were: DECLARE 27% [95% confidence interval (CI) 26.5–27.1]; CANVAS 17% (16.6–17.1); VERTIS 7% (7.1–7.4); and EMPA‐REG 7% (6.5–6.8). Primary care populations fulfilling inclusion criteria were 5–8 years older than trial cohorts, and <10% with inclusion criteria of each trial were prescribed an SGLT‐2i; a greater proportion were men, and of white ethnicity. Conclusions: There was variation in proportions of the primary care type 2 diabetes population fulfilling inclusion criteria of SGLT‐2i CVOTs. The more stringent the inclusion criteria, the lower the proportion identified in a primary care setting. Prescription rates for SGLT‐2is were low in this national database, and there were demographic disparities in prescribing. What's new?: It is unclear to what extent the findings of the sodium–glucose co‐transporter‐2 (SGLT‐2) inhibitor cardiovascular outcomes trials (CVOTs) are generalizable to the real‐world type 2 diabetes populations. Using a national primary care database, we found that the inclusion criteria of four SGLT‐2 inhibitor CVOTs applied to between 7% and 27% of people with type 2 diabetes. Generalizability of the findings from CVOTs to a wider type 2 diabetes population may be restricted to groups defined by the inclusion criteria for each trial. Uniform inclusion criteria for trials would allow direct comparison to be made between trials.